Comparative aerodynamics of synthetic badminton shuttlecocks - Woo, T.-M. T.; Alam, F. (Sports Engineering, 2018)
Badminton synthetic shuttlecocks are known to have significantly different aerodynamic behaviours compared to feathered shuttlecocks due to the difference in designs and use of materials. Given the fragility of avian feathers used for feathered shuttlecocks and the constantly increasing cost of purchase, the interest to assess the current synthetic shuttlecock design as a feasible alternative has re-emerged. The single-piece injection-moulded synthetic shuttlecock has been the mainstream design for the past 50 years; however, little evidence has supported that the design mimics the aerodynamics of feathered shuttlecocks. Recently, a two-part skirt design has emerged proclaiming to have surpassed its synthetic predecessor in regard to matching the aerodynamics of feathered shuttlecocks. In the current study, two different synthetic designs (injection-moulded vs two-part skirt) were benchmarked against a feathered shuttlecock. A wind tunnel test was conducted between 30 and 145 km/h. The drag coefficients of both synthetic shuttlecocks were similar to the feathered shuttlecock up to 105 km/h. Thereafter, the drag coefficient of the injection-moulded design dropped from 0.62 to 0.5 and showing no signs of levelling at speeds over 105 km/h, while the coefficient for two-part skirt design stabilised at approximately 0.55. It was concluded that the two-part skirt design better mimicked the aerodynamics of the feathered shuttlecock.